2014
DOI: 10.1111/bjep.12052
|View full text |Cite
|
Sign up to set email alerts
|

Between students' instrumental goals and how they learn: Goal content is the gap to mind

Abstract: This study extends intrinsic/extrinsic goal research both within education broadly and in the context of Japan. Furthermore, instrumental goals were found to play important roles supporting students in overcoming future motivation deficits and the pursuit of deep approaches to learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 82 publications
(101 reference statements)
2
26
0
Order By: Relevance
“…However, the results reveal a significant negative correlation between scores of learned helplessness and students' attitudes, indicating that the decrease of learned helplessness is related to an increase in positive attitudes. These findings are consistent with those of previous research studies that have found that autonomous motivation has a more significant impact on students' readiness to learn than external motivation and that students who are autonomously motivated find learning more valuable and meaningful (Clayton & Zusho, 2016;Vansteenkiste et al, 2006) and engage in deeper learning (Fryer et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the results reveal a significant negative correlation between scores of learned helplessness and students' attitudes, indicating that the decrease of learned helplessness is related to an increase in positive attitudes. These findings are consistent with those of previous research studies that have found that autonomous motivation has a more significant impact on students' readiness to learn than external motivation and that students who are autonomously motivated find learning more valuable and meaningful (Clayton & Zusho, 2016;Vansteenkiste et al, 2006) and engage in deeper learning (Fryer et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Their confidence and prior experience increase their expectations and belief they will be successful (Bandura, 1994;Ryan & Deci, 2000). Additionally, Fryer et al (2014) found that internally regulated goals were predictors of deep learning and were negatively correlated with effort deficit in undergraduate Japanese students. For a comprehensive review of the different effects intrinsic and extrinsic motivation on college students, see Lei (2010).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For the structural model, β coefficient was interpreted based on the practice as adopted by Fryer, Ginns, and Walker (), in line with Hattie's () guidelines for educational effect sizes. It was interpreted as a small effect size for β = .05, moderate effect size for β = .15 and large effect size for β ≥ .24.…”
Section: Methodsmentioning
confidence: 99%
“…According to Fryer, Ginns and Walker (2014), the role of goals has never been more intensively researched. Within contexts as diverse as the workplace (e.g., Locke & Latham, 2002), sports (e.g., Smith, Ntoumanis, Duda, & Vansteenkiste, 2011), eating disorders (e.g., Verstuyf, Patrick, Vansteenkiste, & Teixeira, 2012), and education (e.g., Huang, Zhang, & Broniarczyk, 2012;Lens & Vansteenkiste, 2008), the importance of goals is clear.…”
Section: Overviewmentioning
confidence: 99%